Development of a School-Based Physical Activity Intervention Using an Integrated Approach: Project SMART - Jung, Yeonhak; Burson, Sheri L.; Julien, Christine; Bray, Dylan F.; Castelli, Darla M. (Frontiers in Psychology, 2021)
Physical activity (PA) is a health-protective factor with multiple benefits for school-age children, yet only 22% of children and adolescents living in the United States (U.S.) accrue the recommended amount of moderate to vigorous PA. Given the prevalence of insufficient PA among children, promoting and providing PA opportunities during the school day, especially when integrated into the curriculum and linked to the learning standards, is essential for children. The purpose of this paper is to describe the procedure for the development of a school-based PA program using an integrated approach through the modified intervention mapping protocol (IMP). A total of 22 physical education teachers and 167 children from five different elementary schools were involved in the process. The procedure includes the Self-Determination Theory (SDT) that provides a theoretical framework that plays a vital role in motivating students to have a physically active lifestyle. This study applied SDT and IMP to develop and pilot a PA intervention called Project SMART using an integrative community participatory approach. As a pilot PA intervention, Project SMART is an online educational game where the students navigate a virtual journey across the U.S. A class’s aggregate PA propels the students on their journey, where standards-based modules are unlocked to achieve STEM (science, technology, engineering, and math) and social-emotional learning outcomes while gaining an understanding of the importance of health behaviors and opportunities to habitually engage in healthy decision-making with the support of their peers. Although initially labor intensive for the researchers, the process of tailoring the intervention to the children's contextual and cultural needs has implications for all theoretically grounded and evidence-based PA interventions.